2021
DOI: 10.3389/pore.2021.1609852
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Gene Prognostic Model of Gastric Cancer Based on Analysis of Tumor Mutation Burden

Abstract: Introduction: Gastric cancer is one of the most common cancers. Although some progress has been made in the treatment of gastric cancer with the improvement of surgical methods and the application of immunotherapy, the prognosis of gastric cancer patients is still unsatisfactory. In recent years, there has been increasing evidence that tumor mutational load (TMB) is strongly associated with survival outcomes and response to immunotherapy. Given the variable response of patients to immunotherapy, it is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Moreover, the high- and low-risk groups exhibited different CNV, TMB, and immune cell infiltration signatures, demonstrating that PRL may play a key modifying role in the regulation of TME and tumor immunity in STAD. In particular, the low-risk group had a higher TMB than the high-risk group, while the low-risk group with a high TMB presented a better prognosis in the STAD cohort, which is consistent with the results of other studies ( 46 , 47 ). Based on the tumor immune editing hypothesis ( 48 ), accompanied by the progression of tumor cells in immunocompetent hosts, fewer immunogenic cancer cells are targeted to evade the antitumor immune response.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the high- and low-risk groups exhibited different CNV, TMB, and immune cell infiltration signatures, demonstrating that PRL may play a key modifying role in the regulation of TME and tumor immunity in STAD. In particular, the low-risk group had a higher TMB than the high-risk group, while the low-risk group with a high TMB presented a better prognosis in the STAD cohort, which is consistent with the results of other studies ( 46 , 47 ). Based on the tumor immune editing hypothesis ( 48 ), accompanied by the progression of tumor cells in immunocompetent hosts, fewer immunogenic cancer cells are targeted to evade the antitumor immune response.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, we found that genomic differences in patients with subgroups were abundant. As is well known, the TMB is associated with tumor immunity, and low TMB is a poor prognostic factor in GC (Roh et al, 2017;Ma et al, 2021). This is consistent with the results of the correlation analysis in our study, where patients in the high-risk group had lower TMB.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of prognosis, the MSI subtype was superior to the microsatellite stable subtype, and this advantage was more significant in the Chinese population ( Cai et al, 2020 ). Ma et al established a prognostic marker of gastric cancer based on 11 TMB differential genes and found that high TMB may promote immune infiltrate, and patients with high TMB showed a better prognosis ( Ma et al, 2021 ). Baseline tumor burden factors, such as the sum of maximum tumor size and target lesion size, can be used in combination with TMB to evaluate the efficacy of immune checkpoint inhibitors in advanced gastric cancer ( Wei X.-L. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of prognosis, the MSI subtype was superior to the microsatellite stable subtype, and this advantage was more significant in the Chinese population (Cai et al, 2020). Ma et al established a prognostic marker of gastric cancer based on 11 TMB differential genes and found that high TMB may promote immune infiltrate, and patients with high TMB showed a better prognosis (Ma et al, 2021).…”
Section: Discussionmentioning
confidence: 99%